2006
DOI: 10.1111/j.1740-0929.2006.00355.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of farm household income levels and rice‐based diet or water hyacinth (Eichhornia crassipes) supplementation on growth/cost performances and meat indexes of growing and finishing pigs in the Mekong Delta of Vietnam

Abstract: An on-farm trial was carried out to improve the current low-income farmers' diet and to assess farm conditions that could accept the new ingredients using locally available feed resources in the Mekong Delta region. A total of 42 local Large White-type pigs, comprising 20 barrows and 22 gilts with initial-to-final mean live weight of 34.2-93.0 kg, were used. The trial was designed as a 3 × 3 factorial with three agricultural gross income levels of seven farm households and three dietary treatments. The annual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
0
11
1
1
Order By: Relevance
“…and Lindberg (2013a) showed that when 50% of soybean protein was replaced with proteins from ensiled Colocasia esculenta, growth performance and carcass traits of local and improved pigs were not affected. Surprisingly, Men et al (2006) report high cost effectiveness of E. crassipes-based diets in Vietnam while this species scored really bad in terms of nutritive value in the present investigation. This allows expecting even higher efficiencies of feeding systems based on low cost forage with higher nutritive value than water hyacinth.…”
Section: Discussioncontrasting
confidence: 74%
“…and Lindberg (2013a) showed that when 50% of soybean protein was replaced with proteins from ensiled Colocasia esculenta, growth performance and carcass traits of local and improved pigs were not affected. Surprisingly, Men et al (2006) report high cost effectiveness of E. crassipes-based diets in Vietnam while this species scored really bad in terms of nutritive value in the present investigation. This allows expecting even higher efficiencies of feeding systems based on low cost forage with higher nutritive value than water hyacinth.…”
Section: Discussioncontrasting
confidence: 74%
“…In the Mekong Delta in Southern Vietnam, pig rearing is the most important income-generating activity among farmer households (Men et al 2006). In recent years, the imbalance between feed and animal product prices had resulted in very low economic returns for the producers.…”
Section: Introductionmentioning
confidence: 99%
“…There are only a limited number of reports on feeding WH to animals. Pigs showed an immediate acceptance of WH without drying ( Men et al, 2006 ) while Islam et al (2011) claimed that a major constraint for its use as a ruminant feed is the high water content. Cattle preferred WH silage containing the highest level of additives, 4 kg dried citrus pulp and 1 kg sugarcane molasses/100 kg pressed WH residue ( Baldwin et al, 1974 ).…”
Section: Discussionmentioning
confidence: 99%
“…Water hyacinth has received much attention in recent years due to its potential benefits as animal fodder, aquafeed, water purification, fertilizer, biogas production, etc. Numerous studies have evaluated WH as a feed source to ruminants ( Baldwin et al, 1975 ; Abdalla et al, 1987 ; Agarwala, 1988 ; Islam et al, 2009 ; Sophal, 2010 ), fish ( Okoye et al, 2002 ; Abdel-Fattah, 2003 ) and other animals ( Dey et al, 1983 ; Men et al, 2002 , 2006 ). Water hyacinth control methods fall into three main categories: physical, chemical and biological ( Julien et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%